2008
DOI: 10.1097/mrr.0b013e32830150f9
|View full text |Cite
|
Sign up to set email alerts
|

The six-minute walk test for children with cerebral palsy

Abstract: The 6-min walk test (6MWT) is increasingly being used as a measure of 'functional ability' in young people with cerebral palsy, despite a lack of published evidence that it is reliable for this population. This study aimed to determine the test-retest reliability of the 6MWT for ambulant 11-17-year-old adolescents with cerebral palsy. Adolescents with cerebral palsy were invited to participate in a single testing session. They performed the 6MWT twice under controlled conditions (standardized 10 m course layou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
125
4
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 7 publications
3
125
4
4
Order By: Relevance
“…Their results also indicated that children who were able to walk longer distances at baseline were more likely to increase their walking distance on retest, thus warranting further investigation of a practice walk in children with a GMFCS level I. A further study by Maher et al [9], which also did not include a practice walk (carried out in children with CP), found a repeatability of 43.1 m with minimal systematic bias (0.85 m) between WTs conducted on the same day. Thus, they also concluded that a practice walk was not necessary before testing.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Their results also indicated that children who were able to walk longer distances at baseline were more likely to increase their walking distance on retest, thus warranting further investigation of a practice walk in children with a GMFCS level I. A further study by Maher et al [9], which also did not include a practice walk (carried out in children with CP), found a repeatability of 43.1 m with minimal systematic bias (0.85 m) between WTs conducted on the same day. Thus, they also concluded that a practice walk was not necessary before testing.…”
Section: Discussionmentioning
confidence: 93%
“…Previous papers on the latter [7][8][9] have documented ICC scores of 0.99, 0.98 and 0.98 Table 1 Means AE S.D. (range) for subject characteristics and study data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Reliability was found for the 6-MWT (ICC=0.93, 0.91, and 0.99 for GMFCS levels I, II, and III respectively). 17,18 For maximal exercise tests, the 10-meter shuttle run tests (SRT-I; for children classified at GMFCS level I [starting speed 5km per h] and SRT-II for children classified at GMFCS level II [starting speed 2km per h]; ICC>0.97) 19 and the McMaster all-out cycle test (r s >0.72-0.92) 4 were the only two tests with published (test-retest) reliability data in CP. One participant provided additional unpublished psychometric data regarding a maximal exercise test (7.5m shuttle walk ⁄ run test) for children classified at GMFCS level III.…”
Section: Results Of Delphi Stagementioning
confidence: 99%
“…The outcome measures were listed within each 40 Walking + + ) 5-MWT a, 41,42 Walking + + ) 6-MWT 17,18 Walking + + ) 8-MWT 43 Walking + + ) 600yd walk ⁄ run test 44 Walking + + ) 30-s walk test 44 Walking + + ) Half-mile walk ⁄ run test 45 Walking + ) ) Arm-cranking ergometer protocol 24 Arm cranking + + ) 5-min treadmill economy test 46 Walking + ) ) EEI-HR overground walk test 13 Walking + ) ) 6-min wheelchair riding test a Riding ) + + Maximal Bruce protocol 47 Walking + ) ) 10m SRT (SRT-I and SRT-II) 19 Walking + ) ) Treadmill test 19 Walking + ) ) Treadmill test 48 Walking + ) ) Treadmill test 38 Walking + ) ) McMaster all-out protocol cycle test 4 Cycling ⁄ arm cranking + + + Ergometer test (cycle or cranking) 49 Cycling of the GMFCS levels (levels I and II were combined because the responses were the same for the two levels). The submaximal exercise test for which reliability and concurrent validity data were found in CP was the 1-minute walk test (MWT; intraclass correlation [ICC]=0.94 for GMFCS levels I, II, III, and IV; significant correlation between Gross Motor Function Measure score and the distance covered during the 1min walk).…”
Section: Results Of Delphi Stagementioning
confidence: 99%